Resilient and reproducible processing for CZTSe solar cells in the range of 10%. (19th July 2018) - Taskesen, Teoman; Steininger, Vincent; Chen, Wenjian; Ohland, Jörg; Mikolajczak, Ulf; Pareek, Devendra; Parisi, Jürgen; Gütay, Levent
Abstract: In this paper, we present our route to fabricate Cu2 ZnSnSe4 (CZTSe) thin films, which allows to achieve reproducible processing of kesterite absorber, that leads to efficiencies in the range of 10%. The article mainly focuses on the annealing process and demonstrates that controlling of the reactor pressure for selenization can be reliably used to tune the losses of volatile constituents in the absorber, enabling adjustments on the properties of the film and solar cell. The findings reveal a noteworthy resilience to small changes of the process parameters in the vicinity of optimum conditions. Interestingly, a certain pressure range for optimum Zn and Sn composition exists, which results in a broad and stable process window and enables reproducible processing of CZTSe with high power conversion efficiencies. The established process also allows simple upscaling of the device area and results in a power conversion efficiency of ≈ 8% on a large area of 2.85 cm 2 . The highest efficiencies achieved by our process are around 11% for smaller lab scale devices. Abstract : In this paper, we present our route to fabricate Cu2 ZnSnSe4 thin films that leads to efficiencies beyond 10%. The paper focuses on the annealing process and demonstrates the existence of a certain pressure region for selenization, which results in a stable and reproducible process window. The presented devices in this work showed a power conversion of 10.7% for 0.33 cm 2 and 7.8% for 2.85 cm 2 cell areas.